Online anti-immigrant discourse in Germany: ethnographically backed analysis of user comments - Nann, Leah; Udupa, Sahana; Wisiorek, Axel (Frontiers in Communication, 2024)
This article investigates discourse- and language-specific features of online anti-immigrant extreme speech in Germany. We analyze a context rich dataset collected and annotated through a collaborative effort involving fact-checkers, ethnographers and natural language processing (NLP) researchers. Using a bottom-up annotation scheme, we capture the nuances of the discourse and develop a typology of lexical innovations. The analysis combines thematic and critical discourse analysis with a linguistic perspective, revealing that direct forms of racism intertwine with argumentative forms of antagonism and playful word games within anti-immigrant discourses, in ways that center around narratives of victimhood and perceived threats from migrants. We further show how the specific conditions in Germany, including strict legal regulations of speech, have shaped the emergence of a non-standard language variety in and through anti-immigrant discourse, which helps the discourse community maintain group identity. The ethnographically backed analysis provides a granular understanding of the phenomenon of online extreme speech in the German context, contributing to the broader field of discourse studies and offering insights into the varieties within anti-immigrant discourse.